Presencia de enfermedad diarreica y respiratoria, en los niños de 2 a 24 meses de edad determinada por la usencia de lactancia materna comparada con los niños que se alimentaron con leche materna exclusiva que acuden al servicio de Consulta Externa del Área de la Salud N° 2 de la Ciudad de Loja en el periodo marzo - septiembre del 2012. - Albarracín Carrión, Mesly Lisbeth (2017)
The Lactancia maternal is the natural food that have to receive the recently been born the first six months of life of exclusive form since it goes to help to warn or reduce the frequency of gastroenteritis and infection of high infection respiratory. Numerous studies realised have showed the association of the absence of lactancia maternal exclusive with the development of these illnesses therefore, has to require the promotion of the practices of feeding with maternal milk from the birth with the purpose to diminish the risk to present these pathologies. With the main purpose to establish the relation between the absence of lactancia maternal and the apparition of in Illness diarreica a cute and high respiratory infection; it realized a descriptive study, prospective, quantitative and of transversal court, to a group of 183 lower boys of 2 years, by means of the preparation of a survey that realise them to the mothers of the patients studied. Finalised the investigation determined that 69% of the lactantes studied did not feed with maternal milk from his birth whereas 31% received lactancia maternal exclusive. Inside the causes for the suspension of the same, identified that the scarce production of milk this in the first place with 37%, followed of labour situations with 25% and of lactancia painful in or 12%. It could to evidence besides the relation that has the feeding with exclusive maternal milk and the presence of illness diarreica, since had 13 boys that presented the pathology versus those that did not feed with maternal milk scoop that went 87 boys. Besides, could establish that the infection of respiratory tract high presented in a lower number in boys that suckled with maternal milk obtaining 24 cases in relation with the 95 boys that presented the pathology in absence of lactancia maternal exclusive.